Do people with Alzheimer's disease improve with repeated testing? Unpacking the role of content and context in retest effects. (17th August 2018) - Gross, Alden L; Chu, Nadia; Anderson, Loretta; Glymour, M Maria; Jones, Richard N; ,
Abstract: Objective: retest effects may be attributed to 'repeated content' in neuropsychological tests such as words in word list-learning tests, or the 'testing context' which involves procedural memory and reduced test anxiety following repeated administration. Alzheimer's Disease (AD) severely impairs episodic memory, so longitudinal cognitive testing among people with dementia may reveal the relative contributions of content versus context to retest effects in neuropsychological testing. Method: we used data from the Critical Path Institute's repository of placebo arm data from randomized controlled trials (RCTs) of dementia conducted by participating pharmaceutical companies ( N = 990 people, 4, 170 study visits, up to 2.4 years of follow-up). To estimate retest effects on the Mini-Mental State Examination (MMSE), we used linear regressions with random effects for people and time, adjusting for age, sex and race, and longitudinal quantile regressions. Results: average MMSE score (16.6 points, SD = 5.5, range 1, 27) declined by 2.0 points/year (95% confidence interval, CI: −2.3, −1.8). Mean retest effect was 0.6 points (95% CI: 0.4, 0.8) at second assessment (average 4 months after baseline). Retest effects were similar among participants with and without any recall on the short-delay word recall subscale score at baseline, and at the 30th, 50th and 70th percentiles of the MMSE distribution, suggesting similar retest effects across the spectrum from mild to severe cases of dementia. Conclusions: retest effects are apparent in people with dementia despite reduced episodic memory, suggesting a prominent role of the testing context in RCTs and cohort studies.